Mycorrhizal fungi affect plant growth: experimental evidence comparing native and invasive hosts in the context of forest fragmentation - Grilli, Gabriel (2014)
Forest fragmentation and biological invasions modify plant–mycorrhizal fungal interactions, but how these variations affect native and invasive plant vegetative and reproductive growth in a fragmented forest remain unknown. To test the effects of soil fungi from different forest fragment sizes on native and invasive plants, we conducted a greenhouse factorial experiment combining soil source (i.e., small and large forest fragments) and fungicide application (with and without fungicide) on two ruderal congeneric Euphorbia (E. acerensis and E. dentata, native and invasive, respectively). Soil fungi from small forest fragments promoted lower rates of mycorrhizal colonization than soil from large forest fragments in both plant species. In general, the source of soil fungi had no effect on vegetative and reproductive growth of both plant species. Fungicide application positively affected plant height and dry mass of the native host, while the fungicide application negatively affected height and neutrally affected growth of the invasive plant species. Reproductive traits were in general positively affected by fungicide application, although in some cases, they were dependent on soil source. Forest fragmentation might promote changes in soil conditions that negatively affect mycorrhizal colonization at levels without functional consequences for plant growth. However, landscape modifications that contribute to a more severe reduction in Arbuscular Mycorrhizal (AM) fungal colonization might certainly have important consequences on native and invasive plant growth.